The binomial theorem or binomial expansion desribes the algebraic expansion of powers of a binomial. The teorem states that it is possible to expand the polynomial \((x+y)^n\) into a sum that includes terms \(ax^by^c\). The coefficient \(a\) in term \(ax^by^c\) is binomial coefficient while \(b\) and \(c\) are nonegative integers whose sum gives number \(n\) i.e. \(b+c = n\).
For positive integer n:
\begin{eqnarray}(x+y)^n &=& \binom{n}{0}x^ny^0 + \binom{n}{1}x^{n-1}y^1 + \binom{n}{2}x^{n-2} y^2+...+\binom{n}{n-1}x^1 y^{n-1} + \binom{n}{n} x^0 y^n\\ (x+y)^n &=& \sum_{k = 0}^n \binom{n}{k} x^{n-k}b^k. \end{eqnarray} The properties of binomial coefficient are:
- the developt binomial has \(n+1\) members,
- exponents with base \(x\) decreasse from \(n\) to 0 while the exponennt with base \(y\) increase from 0 to \(n\), their sum in every member is equal to n.
- if we observe the formula from left and right side at the same time we can see that binomial coefficient are symmetric (the value is equal).
- the symetry property $$ \binom{n}{k} = \binom{n}{n-k} $$ For example \(\binom{14}{10} = \binom{14}{4}\)
- the Pascal's triangle property $$\binom{n}{k-1} + \binom{n}{k} = \binom{n+1}{k} $$ For example: \(\binom{7}{3} + \binom{7}{4} = \binom{8}{4}\)
Binomial theorem and Binomial coefficients - Examples
- Example 1 Write the following expression \((x+y)^2\) in the expanded form using binomial theorem. $$\begin{eqnarray}(x+y)^2 &=& x^2 + 2x^{2-1} y + y^2 = x^2 + 2xy + y^2\end{eqnarray}$$ Example 2 Write the following expression \((x+y)^3\) in the expanded form using binomial theorem. $$ \begin{eqnarray}(x+y)^3 &=& x^3 + 3x^{3-1}y + \frac{3(3-1)}{2!}x^{3-2}y^2 + \frac{3(3-1)(3-2)}{3!}x^{3-3}y^3 \\\nonumber (x+y)^3 &=& x^3 + 3x^2 y + 3xy^2 + y^3\end{eqnarray}$$ Example 3 Write the following expression \((x+y)^4\) in the expanded form using binomial theorem. $$ \begin{eqnarray}(x+y)^4 &=& x^4 + 4x^{4-1}y + \frac{4(4-1)}{2!}x^{4-2}y^2 + \frac{4(4-1)(4-2)}{3!}x^{4-3}y^3 + \frac{4(4-1)(4-2)(4-3)}{4!}x^{4-4}y^4 \\ \nonumber (x+y)^4 &=& x^4 + 4x^3y+ 6x^2y^2 + 8xy^3 + y^4\end{eqnarray}$$ Example 4 Write the following expression \((x+y)^6\) in expanded form. $$\begin{eqnarray}(x+y)^6 &=& x^6 + 6x^5y + \frac{6(6-1)}{2!}x^{6-2}y^2 + \frac{6(6-1)(6-2)}{3!}x^{6-3}y^3 \\ \nonumber &+& \frac{6(6-1)(6-2)(6-3)}{4!}x^{6-4}y^4 + \frac{6(6-1)(6-2)(6-3)(6-4)}{5!}x^{6-5}y^5 \\ \nonumber &+&\frac{6(6-1)(6-2)(6-2)(6-3)(6-4)(6-5)}{6!}y^6\\\nonumber (x+y)^6 &=& x^6 + 6x^5y + 15x^4y^2 + 20x^3y^3+15x^2 y^4 + 6xy^5 + y^6\end{eqnarray}$$
- Example 5 Solve the equation \(\binom{n}{6} = \binom{n}{5}\)
Solution $$\begin{eqnarray}\frac{n!}{(n-6)!6!} &=&\frac{n!}{(n-5)!5!}\\ \nonumber \frac{n(n-1)(n-2)(n-3)(n-4)(n-5)(n-6)!}{(n-6)!6!} &=& \frac{n(n-1)(n-2)(n-3)(n-4)(n-5)!}{(n-5)!5!}\\\nonumber \frac{n-5}{6\cdot 5!} &=& \frac{1}{5!} \\\nonumber n-5 &=& 6 \\\nonumber n &=& 11 \end{eqnarray}$$ - Example 6 Solve the equation\(\binom{n}{4} + \binom{n}{5} = \binom{17}{5}\)
Solution $$ \begin{eqnarray} \binom{n}{4} + \binom{n}{5} &=& \binom{17}{5} \\ \nonumber \end{eqnarray}$$ In this example the \(n\) can be found by applying Pascal's trinagle property. The formula of Pascal's triangle can be written as $$\binom{n}{k-1} + \binom{n}{k} = \binom{n+1}{k} $$. By comparing Pascals triangle property with our example we can conclude that \(k = 5\) and \(n+1 = 17 \Rightarrow n = 16\) - Example 7 Which term in order of development of binomial \(\left(x^2 + y^3\right)^5\) contains \(x^6y^6\)?
Solution The general term of development $$ A_{k+1} = \binom{5}{k}(x^2)^{5-k}(y^3)^k = \binom{5}{k}x^{10-2k}y^{3k}$$ To determine \(k\) we equate the exponents with the bases \begin{eqnarray} 10-2k &=& 6 \Rightarrow -2k = -4/:(-2) \Rightarrow k = 2\\ 3k &=& 6/:3 \Rightarrow k = 2\end{eqnarray} The \(x^6y^6\) is the third member. - Example 8 Determine the coefficient in development of binomial \(\left(3+4x\right)^6\) which contains \(x^3\)
Solution\begin{eqnarray}A_{k+1} &=& \binom{6}{k}3^{6-k}(4x)^k = \binom{6}{k}3^{6-k}4^kx^k\\ x^k &=& x^3 \Rightarrow k = 3\\ \binom{6}{3}&\cdot & 3^3\cdot 4^3 \cdot x^3 = 20\cdot 27 \cdot 64\cdot x^3 = 34560 x^3\end{eqnarray} The coefficient which is next to \(x^3\) is 34560. - Example 9 If a binomial coefficient of third member of binomial \(\left(9x - \frac{1}{\sqrt{3x}}\right)^n\)is equal to 105, determine the thirtheenth member.
Solution From description of the problem we know that the third member is equal to 105. \begin{eqnarray}\require{cancel} \binom{n}{2} &=& 105 \\ \frac{n!}{(n-2)! 2!} &=& 105 \\ \frac{n(n-1)\cancel{(n-2)!}}{\cancel{(n-2)!}2} &=& 105/\cdot 2\\ n(n-1) &=& 210 \\ n^2 - n - 210 &=& 0 \\ n_{1,2} &=& \frac{1 \pm \sqrt{1 + 4*210}}{2} \\ n_{1,2} &=& \frac{1 \pm 29}{2} \\ n_1 &=& 15 \\ \cancel{n_2 = -14} \end{eqnarray} The thirtheen member is calculated using formula for general member \begin{eqnarray}A_{13} &=& \binom{15}{12} (9x)^3 \left((3x)^{-\frac{1}{2}}\right)^{12}\\ A_{13} &=& 455 \cdot 3^6x^3 (3x)^{-6}\\ A_{13} &=& 455 x^{-3}\end{eqnarray} - Example 10 Calculate using binomial formula \(0.95^5\) of four decimal places.
Solution \begin{eqnarray}0.95^5 &=& (1-0.05)^5\\ 0.95^5 &=& 1*5\cdot 0.05 + 10\cdot 0.05^2 - 10\cdot 0.05^3 + 5\cdot 0.05^4 - 0.05^5 = 0.7738\end{eqnarray}
No comments:
Post a Comment